PENGUATAN SOFT SKILL DAN KETAHANMALANGAN (Adversity Quation) DENGAN PENDEKATAN BUDAYA LOKAL SPIRITUAL DALAM PENGEMBANGAN GOOD CHARACTER SISWA - Dewa Gede Sastra Wiguna (Widyadari : Jurnal Pendidikan, 2020)
Education is a process of change in the development of knowledge (cognitive), skills (psychomotor) and attitudes (affective) person, then education should produce an output proportional to the ability of the hard skills and soft skills. In addition to the curriculum which has a charge that is lower than the soft skills payload hard skills, soft skills with the imbalance between hard skills can also be caused by a learning process that emphasizes the acquisition value of test results and the value of the test results. Globalization (without limit) create an atmosphere of competition in life is getting tougher. Only people who are competitive, not easily discouraged and ready to accept the challenge that will be successful in life. So people with low adversity Quation will run over time, while those with high adverity Quation will be successful and become a winner. The success of a person is not only determined by IQ (Intelligence quation) but also by adversity quotient (AQ) owned. Bali has a wide range of spiritual culture that can be used as a shield themselves from a variety of negative effects that harm. For it to develop spiritual culture at the level of soft skills and adversity Quation, a person is able to optimize towards the positive character development for the realization of qualified human resources in accordance with national education goals.